The next wave: popularity of e-wallet?? - Neoh, May Ying; Riri Andri Ani, Mustafa Tan; Tan, Shir Lynn; Tean, Sim Yin; Wong, Phooi Wai (2019)
This study was studies the relationship between perceived security, perceived usefulness, perceived ease of use, subjective norm, perceived trust and intention to use E-Wallets. The target respondents of this study were included 300 people that own E-Wallet with the sampling location at Kampar, Malaysia. To execute the five statistics results were cronbach’s alpha, composite reliability, average variance extracted, discriminant validity, as well as hypothesis testing. The Partial Least Squares Structural Equation Modeling (PLS-SEM) had been conducted in this study. The results found that there were significant relationship between perceived security, perceived usefulness, perceived ease of use, subjective norm, perceived trust and intention to use E-Wallets. This study was provided the benefit to the society such as consumer of E-Wallets, developer of E-Wallets, policymaker and government of Malaysia.